Targeting CD38/ ADP-ribosyl cyclase as a novel therapeutic strategy for identification of three potent agonists for leukopenia treatment - Yuanzhi Liu; Linwei Zhang; Long Wang; Xiaoqin Tang; Shengli Wan; Qianqian Huang; Mei Ran; Hongping Shen; Yan Yang; Sawitree Chiampanichayakul; Singkome Tima; Songyot Anuchapreeda; et al. (Elsevier, 2024)
Leukopenia is the most common side effect of chemotherapy and radiotherapy. It potentially deteriorates into a life-threatening complication in cancer patients. Despite several agents being approved for clinical administration, there are still high incidences of pathogen-related disease due to a lack of functional immune cells. ADP-ribosyl cyclase of CD38 displays a regulatory effect on leukopoiesis and the immune system. To explore whether the ADP-ribosyl cyclase was a potential therapeutic target of leukopenia. We established a drug screening model based on an ADP-ribosyl cyclase-based pharmacophore generation algorithm and discovered three novel ADP-ribosyl cyclase agonists: ziyuglycoside II (ZGSII), brevifolincarboxylic acid (BA), and 3,4-dihydroxy-5-methoxybenzoic acid (DMA). Then, in vitro experiments demonstrated that these three natural compounds significantly promoted myeloid differentiation and antibacterial activity in NB4 cells. In vivo, experiments confirmed that the compounds also stimulated the recovery of leukocytes in irradiation-induced mice and zebrafish. The mechanism was investigated by network pharmacology, and the top 12 biological processes and the top 20 signaling pathways were obtained by intersecting target genes among ZGSII, BA, DMA, and leukopenia. The potential signaling molecules involved were further explored through experiments. Finally, the ADP-ribosyl cyclase agonists (ZGSII, BA, and DMA) has been found to regenerate microbicidal myeloid cells to effectively ameliorate leukopenia-associated infection by activating CD38/ADP-ribosyl cyclase-Ca2+-NFAT. In summary, this study constructs a drug screening model to discover active compounds against leukopenia, reveals the critical roles of ADP-ribosyl cyclase in promoting myeloid differentiation and the immune response, and provides a promising strategy for the treatment of radiation-induced leukopenia.